2021
DOI: 10.3390/ijerph18052241
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Based on the Walking Test and Telerehabilitation Improved Cardiorespiratory Fitness in People Diagnosed with Coronary Heart Disease during the COVID-19 Pandemic

Abstract: This study investigated an alternative home-based cardiac telerehabilitation model in consideration of the recommendations for the COVID-19 quarantine of people diagnosed with coronary heart disease (CHD). We hypothesized that using a 200 m fast walking test (200 mFWT) and telerehabilitation would create an effective alternative cardiac rehabilitation (CR) intervention that could improve cardiorespiratory fitness. Participants (n = 19, mean age 60.4 ± 9.6) of the 8-week intervention performed regular physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
2
12
0
7
Order By: Relevance
“…From the eight articles reviewed, it is known that physical therapy services through telemedicine or telerehabilitation have produced good results for their users during the Covid-19 pandemic. This method has been successfully applied to patients with cardiorespiratory disorders, patients with musculoskeletal disorders (Patellofemoral Pain Syndrome and breast cancer), as well as patients with neurological disorders (Stroke, and Amyotrophic Lateral Sclerosis) (Albornoz-Cabello et al, 2021;Batalik et al, 2021;De Marchi et al, 2021;Hameed et al, 2021;Lewis et al, 2021;Mella-Abarca et al, 2020;Miao et al, 2021;Turcinovic et…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the eight articles reviewed, it is known that physical therapy services through telemedicine or telerehabilitation have produced good results for their users during the Covid-19 pandemic. This method has been successfully applied to patients with cardiorespiratory disorders, patients with musculoskeletal disorders (Patellofemoral Pain Syndrome and breast cancer), as well as patients with neurological disorders (Stroke, and Amyotrophic Lateral Sclerosis) (Albornoz-Cabello et al, 2021;Batalik et al, 2021;De Marchi et al, 2021;Hameed et al, 2021;Lewis et al, 2021;Mella-Abarca et al, 2020;Miao et al, 2021;Turcinovic et…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it turns out that this method has other advantages. One of them is cost-effective (Batalik et al, 2021;Miao et al, 2021). Telerehabilitation showed to be at least as cost-effective as traditional cardiac rehabilitation programs (Kraal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this point has been comprehensively reviewed in a position statement by the EAPC, novel insights (as discussed above) could also add interesting data[ 11 , 42 , 120 , 121 ]. While exercise testing (namely cardiopulmonary exercise stress testing) has a central role, other methods have also been described as of potential interest[ 11 , 42 , 90 , 123 , 124 ]. In this regard, the use of the 6-min walk test in assessing exercise progression has been proposed, whereas another recent study (albeit in a small number of individuals) reported on the use of the 200-m fast walking test in tailoring exercise in low to moderate risk CHD patients undergoing HBCR[ 123 , 124 ].…”
Section: Future Perspectivementioning
confidence: 99%